Focusing on the essentials: learning for performance - Murphy Catherine J (BMC, 2008)
Abstract As The World health report 2006 emphasized, there is increasing consensus that training programmes should focus on "know-how" instead of "know-all." Health workers need to know how to do the job they will be expected to do. IntraHealth International's Learning for performance: a guide and toolkit for health worker training and education programs offers a step-by-step, customizable approach designed to develop the right skills linked to job responsibilities. Using Learning for performance (LFP) yields more efficient training that focuses on what is essential for health workers to do their jobs and on effective learning methods, while addressing the factors that ensure application of new skills on the job. This brief communication describes the Learning for performance approach and initial findings from its application for pre-service education and in-service training in three countries: India, Mali and Bangladesh. Based on IntraHealth's experiences, the author provides thoughts on how LFP's performance-based learning approach can be a useful tool in training scale-up to strengthen human resources for health.